Your Digital Afterlives - Steinhart, E. author. aut Link
XIII, 259 p.
Keywords: Digitalism is a philosophical strategy that uses new computational ways of thinking to develop naturalistic but meaningful ways of thinking about bodies, souls, universes, gods, and life after death. Your Digital Afterlives examines four recently developed and digitally inspired theories of life after death.